Design Analysis of Array of Dipole Transmitters for Wireless Power Transfer - Junior Milembolo Miantezila; Victor Adewuyi; Eunice Owoola (EMITTER International Journal of Engineering Technology, 2022)
Considered in this work are the radiation aspects of a radio-frequency wireless power transfer system. Using the halfwave dipole as a candidate of choice, the current distribution on the antenna is first evaluated and presented using the versatile electromagnetic numerical Method of Moment technique (MoM). Using the current distribution obtained from the kernel of integration, the radiation fields for the single dipole element was obtained. Also, the analysis is extended to uniformly space linear antenna arrays using broadside and ordinary endfire arrays as candidates of interest. The simulation results for the broadside and endfire arrays were presented for 5, 6, 7, 10, 20 and 30 array elements at 0.3, 0.4 and 0.5 inter-element spacing. The peak directivity of broadside array occurs at 30 elements, 0.5λ spacing, and exceeds endfire array peak directivity by 11.27%. In addition to the advantage of an improved directivity achieved by the 7-element broadside array, an improved peak sidelobe level (PSLL) with the lowest PSLL for 7, 20, and 30 elements broadside array occurring at -12.0534 dB, -12.4298 dB, -12.6642 dB, -13.2246 dB, and -13.2747 dB respectively.